Preconception Mental Health, Socioeconomic Status, and Pregnancy Outcomes in Primiparous Women - Björkstedt, Satu-Maarit; Koponen, Hannu; Kautiainen, Hannu; Gissler, Mika; Pennanen, Pirjo; Eriksson, Johan G.; Laine, Merja K. (Frontiers in Public Health, 2022)
Background One in four women in childbearing age has some degree mental disorders and are therefore prone to both pregnancy complications and adverse health outcomes in their offspring. Our aim was to evaluate the impact of preconception severe mental disorders on pregnancy outcomes in primiparous women. Methods The study cohort was composed of 6189 Finnish primiparous women without previously diagnosed diabetes who delivered between 2009 and 2015 living in the city Vantaa, Finland. Women were classified to have a preconception serious mental disorder if they had one or more outpatient visits a psychiatrist or hospitalization with a psychiatric diagnosis one year before conception. Data on pregnancies, diagnoses, and pregnancy outcomes were obtained from national registers at an individual level. Results Primiparous women with preconception serious psychiatric diagnosis were younger, more often living alone, smokers, and had lower educational attainment and lower taxable income than women without psychiatric diagnosis (for all p<0.001). Of all women, 3.4% had at least one psychiatric diagnosis. The most common psychiatric diagnoses were depression and anxiety disorders. The most common comorbidity was the combination of depression and anxiety disorders. There were no differences in the need of respiratory treatments, admissions to neonatal intensive care unit or antibiotic treatments between the offspring´s groups. Conclusions Although primiparous women had serious mental disorders, the well-being of newborn was good. The most common serious mental health disorders were depression and anxiety disorders, and the psychiatric comorbidity was common. Women with serious mental disorders more often belonged to lower socioeconomic groups.